'I Cannot Stand up to my Chief nor the State': Reflections on Development-Induced Housing Mobility in Pro-Poor Housing Systems in Tamale, Ghana. Issue 2 (3rd April 2021) - Yakubu, Ibrahim; Spocter, Manfred; Donaldson, Ronnie
ABSTRACT: In Ghana, housing practices for the majority of urban residents lie outside the scope of formal housing markets and planning regulations. This has made urban upgrading a key component of physical development in cities in Ghana. In the face of accelerated urbanisation and the corresponding upsurge in informal housing practices, local authorities continue to grapple with the challenges of negotiating and implementing upgrading programmes without compromising pro-poor housing systems. As cities grow, mainly through the accretion of rural settlement nuclei, the quest to achieve orderly physical development has meant that new development ought to be planned alongside the upgrading and/or realignment of existing settlements. This complex spatial development trajectory makes forced residential mobility an integral component of post-independence urban development initiatives in many towns. Based on interviews with selected households and key stakeholders at city and neighbourhood levels, this study critically examines the incidence of development-induced residential mobility practices in the pro-poor housing systems of Tamale, Ghana. It makes a significant contribution to our understanding of the operation of dual urban management systems and how the navigation of such systems can be frustrating. The results show how and why sub-district local government actors collaborate with traditional chieftaincies to compel the relocation of poor families under the pretence of providing access roads. Paved roads have thus become deeply engrained in the housing politics of low-income communities, and form part of the narratives of the success or failure of chiefs or elected local government representatives. It is recommended that the scope of stakeholder engagement be broadened to promote inclusive urban development in Tamale.